First description of early developmental stages of the native invasive fireworm Hermodice carunculata (Annelida, Amphinomidae): a cue to the warming of the Mediterranean Sea - TOSO, ANDREA; BOULAMAIL, SARAH; LAGO, NICOLA; PIERRI, CATALDO; PIRAINO, STEFANO; GIANGRANDE, ADRIANA (Mediterranean Marine Science, 2020)
Observations on the reproductive behavior and larval development of the bristled fireworm Hermodice carunculata, a common inhabitant of shallow marine rocky bottoms in the Southern Mediterranean Sea, are reported here. In recent years, an increase in abundance and a northward expansion of the populations along the Southern Italian coast were jointly detected, presumably linked to rising water temperature in the Mediterranean Sea. After making in situ observations on two consecutive spawning events, live worms and fresh spawn were brought into the lab, kept at either 27 ºC or 22 ºC and followed through development. Complete and normal development was observed only at 27°C. By contrast, embryonic and larval development appeared to be slowed down at 22°C, stopping at the protrochophora stage. Early development of H. carunculata suggests the existence of a long pre-metamorphic, planktotrophic period in the water column that can explain the genetic cohesion of this species and the low genetic divergence found among populations across the Atlantic Ocean. The observed increase in abundance, invasiveness potential, and geographical northern distribution of the bearded fireworms is probably determined by a progressive northward latitudinal shift of the sea surface temperature coincident with the temperature threshold required for the developmental and reproductive success of the worm.